GRAMMATICAL COHESION IN THE SUSILO BAMBANG YUDHOYONO'S SPEECH ENTITLED "TOWARDS HARMONY AMONG CIVILIZATION" - Sarang, Patrisius; Sulatra, I Komang (LITERA : Jurnal Bahasa Dan Sastra, 2024)
The purpose of this study was to determine the types of grammatical cohesion used and to analyze how grammatical cohesion is applied "Towards Harmony among Civilizations" published on September 29, 2009 about the new era of world order at Harvard University. This study discusses discourse analysis, especially cohesion analysis. Hassan and Halliday (1976) theories related to literature, discourse, cohesion, and speech were used to obtain the objectives of this study. This research is qualitative research using the observation method. In this study the data obtained by using data collection techniques in the form of documentation. Data collection procedures include searching, selecting, reading, and identifying data. In analyzing, data is collected by reading and grouping them into paragraphs. Cohesion analysis was carried out to determine the type of cohesion contained in the speech text. Arguments are also given to support the comparison between theory and analysis. The researcher found that the types of grammatical cohesion used in speech consisted of references, ellipsis, and conjunctions. Found references (305), found ellipsis (1), and found conjunctions (244). From the results of this study, it can be concluded that in Susilo Bambang Yudhoyono's speech, he used the cohesion reference type.